The ethical dimension of ecological thinking and action in early childhood education - Buchcic, Elżbieta; Żeber–Dzikowska, Ilona (Studia Ecologiae et Bioethicae, 2013)
This paper provides an analysis of selected topics in the field of eco-ethics. The school should be more involved in the protection of the natural environment, mainly by shaping truly responsible attitudes. Ecological education must become an integral part of a person’s upbringing. The aim of education should be to create and develop correct pro-ecological attitudes, which are opposed to the uncontrolled exploitation of natural resources. Environmental sustainability is only possible if people are persuaded to give up the consumer lifestyle (the so-called ecological asceticism).